The Relationship Between Technological Environment And The Effectiveness of Accredited Private Madrasah Aliyah in Riau Province - As'ad Tabi'in; Muntholib; Lukman Hakim (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This study aims to examine the relationship between the technological environment and the effectiveness of accredited Private Aliyah Madrasah A in Riau Province both partially and simultaneously. This research is a quantitative study with a survey method conducted at Private Aliyah Madrasahs in Riau Province. population of 79 people and samples using random sampling. The hypothesis in this study is: technological environment has a significant relationship both partially and simultaneously to the effectiveness of madrasah. Hypothesis testing uses Pearson Product Moment Correlation and multiple regression technique analysis, with a significance level of alpha 5 percent (α=0.05). This study results in findings, namely: technological environment has a significant relationship with madrasah effectiveness. Based on the research findings, it can be concluded that: the technological environment variable contributes significantly to the effectiveness of madrasah, namely the value of tcount (5.879) > ttabel (1.991) so that H0 is rejected and H1 is accepted, which means that the technological environment provides a significant relationship to the effectiveness of madrasah.